Supply chain coordination under revenue-sharing contract with value-added services considering risk-attitude of the customers. (2018) - Gamchi, Nafiseh Shamsi; Torabi, Seyed Ali
In this paper, we address a dual-channel supply chain in which a manufacturer sells multiple products via both a direct channel (like an online market) and indirect channels (e.g., through some retailers). Different service contracts with different risk-attitudes are offered by different channels as product arranty. A decentralised and a centralised model (under revenue-sharing contract) are discussed to obtain the sale price of each product at each channel. Two coordinating factors, namely the wholesale price and the fraction of revenue, are obtained as decision variable and using 'Shapley value' respectively. Finally, a numerical example is presented to illustrate the applicability of the proposed decision models.